The Integration Dilemma: Navigating the Challenges of AI in Existing Hospital Systems - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Integration Dilemma: Navigating the Challenges of AI in Existing Hospital Systems The promise of Artificial Intelligence (AI) in healthcare is trans...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care